A study on working capital in hospital institutions Un estudio acerca de las necesidades de capital de giro en instituciones hospitalarias - Pereira, Ana Cristina; Carrera Maia, Anselmo (O Mundo da Saúde, 2006)
The objective of this exploratory and descriptive study was to investigate how health organizations have financed their working capital necessities. A bibliographical research was followed by a documentary research on a set of 2000 and 2001 years Financial Statements of health corporations published in periodical publications of a broad circulation. The research universe was constituted by profit-seeking health corporations that provide hospital heath services. Data from thirteen companies were collected. Collected data processing was done in three stages: 1) a calculation of net (circulating) working capital (CCL) and liquidity ratios; 2) reclassification of Balance Sheet accounts according to Fleuriet model; 3) calculation of 0 variable NCG (working capital needs), NTFP (permanent financing - total necessities) and ST (total balance). One discovered that a) most analyzed companies had capacity to liquidate their short term debts; b) operational liabilities financed all operational assets; c) working capital necessities were not financed by short term financial resources. The universe of thirteen companies limited getting to broader conclusions on these companies realities, but the work presented the available tools to assist a working capital more efficient management.